Influence of compression forces on tablets disintegration by AC Biosusceptometry - Cora, Luciana A. [UNESP]; Fonseca, Paulo R. [UNESP]; Americo, Madileine F.; Oliveira, Ricardo B.; Baffa, Oswaldo; Miranda, Jose Ricardo A. [UNESP] (Elsevier B.V., 2008)
Analysis of physical phenomena that occurs during tablet disintegration has been studied by several experimental approaches; however none of them satisfactorily describe this process. The aim of this study was to investigate the influence of compression force on the tablets by associating the AC Biosusceptometry with consolidated methods in order to validate the biomagnetic technique as a tool for quality control in pharmaceutical processes.Tablets obtained at five compression levels were submitted to mechanical properties tests. For uncoated tablets, water uptake and disintegration force measurements were performed in order to compare with magnetic data. For coated tablets, magnetic measurements were carried out to establish a relationship between physical parameters of the disintegration process. According to the results, differences between the compression levels were found for water uptake, force development and magnetic area variation measurements. ACB method was able to estimate the disintegration properties as well as the kinetics of disintegration process for uncoated and coated tablets. This study provided a new approach for in vitro investigation and validated this biomagnetic technique as a tool for quality control for pharmaceutical industry. Moreover, using ACB will also be possible to test these parameters in humans allowing to establish an in vitro/in vivo correlation (IVIVC). (C) 2007 Elsevier B.V. All rights reserved.
Keywords: AC Biosusceptometry; compression force; disintegration force; water uptake; magnetic tablets; disintegration